THE ROLE OF SOCIAL CAPITAL ON TREATMENT COMPLIANCE IN HIV-AIDS PATIENTS - Susmiati; Indah Jayani; Yeni Lufiana Novita Agnes; Devangga Darma Karingga; Kun Ika Nur Rahayu (Nursing Sciences Journal, 2026)
Lack of medication adherence in HIV-AIDS patients results in serious complications and even death. A social network approach is needed to improve medication adherence behavior. The purpose of this study was to determine the relationship between social capital and medication adherence in HIV-AIDS patients in the Kediri area. Eighty respondents were obtained using a purposive sampling technique with the inclusion criteria of HIV-AIDS patients aged 10 to 750 years, cooperative and communicative, and able to read and write. The instrument used to measure social capital and medication adherence was a questionnaire with a reliability and validity of Cronbach's Alpha at 0.8. Data analysis used the Spearman rank test with a significance level of 0.05. The results showed a relationship between social capital and medication adherence in HIV-AIDS patients with a very strong correlation value (r = 0.811). Efforts are needed to increase social capital from various aspects of the social network to improve medication adherence in HIV-AIDS patients.